Prevalence and impacts of self-medication in a disadvantaged setting: the importance of multi-dimensional health interventions - Nguyen, Cuong Tat; Nguyen, Hien Thu; Boyer, Laurent; Auquier, Pascal; Fond, Guillaume; Do, Khanh Nam; Dang, Anh Kim; Do, Huyen Phuc; Latkin, Carl A.; Ho, Roger C. M.; Ho, Cyrus S. H. (Frontiers in Public Health, 2023)
Background Self-medication is recognized as an effective form of treatment and is increasingly encouraged to treat minor illnesses. However, misuse of self-medication leaves devastating impacts on human health and causes antimicrobial resistance. Using medication without a prescription among farmers could cause more severe effects on their health than non-farm workers since they suffer from several occupational hazards such as excessive exposure to pesticides. Methods A cross-sectional study was conducted in 197 residents living in Moc Chau from August to September. A structured questionnaire and face-to-face were used to collecting data. The multivariate logistic model was applied to indicate associated factors with the self-medication. Results The prevalence of self-medication among farmers was 67%. Pain relievers (66.7%) and antibiotics (32.5%) were the types of medicines that were the most commonly purchased and used without a medical prescription. Ethnics and health status also significantly affected the self-medication practice as well as the purchase and use of antibiotics. The distance to travel to a medical center and the dangerous or difficult travel, participants with arthritis or inpatient treatment had significantly associated with buying and using the medicine and antibiotics without the medical prescription of farmers. Conclusion Our research highlights a considerably high prevalence of self-medication among farmers residing in the mountainous area of Vietnam. Individual factors such as ethnics, health status, distance to health centers, and dangerous or difficult travel were found to be related to the SM practice as well as the purchase and use of antibiotics. From that, the current study suggests interventions. For instance, official guidelines are needed to raise awareness and minimize the disadvantages of self-medication; and digital health technologies should be applied to reduce the gap in healthcare service between mountainous and other areas of Vietnam.